Automotive Technology Program of State Universities and Colleges Regarding Curriculum and Instruction, Adherence To Quality Assurance Standards, and Graduates' Employability - Perry Ferdinan Carpucio (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2024)
This study examined the significance of the automotive technology program of state universities and colleges in the Bicol Region as a basis for curriculum improvement. The assessment analyzed the SUC Automotive Technology Program's faculty qualifications and laboratory facilities, alongside the program's curriculum and instructional status, adherence to quality assurance protocols, and the employability of its graduates. This research study utilized a descriptive survey methodology. The questionnaires serve as the primary instruments for data collection. Frequency, percentage, and general mean are the statistical methods employed in analyzing the acquired data. The study comprised four groups of respondents: BSIT majors in Automotive Technology and BSAT students participating in industry immersion/supervised industry training during AY 2022-2023; core faculty members in automotive technology from five SUCs; graduates from AY 2020-2021 and 2021-2022; and automotive industry partners of the aforementioned SUCs, represented by their service advisors and technicians. It was disclosed that the majority of the academics lack the requisite industry experience mandated by CMO 76, s. 2017. Similarly, the qualifications of professors as trainers in automotive disciplines and the availability of automotive equipment do not entirely satisfy the regulatory requirements. The SUCs failed to adhere to CHED and TESDA standards regarding laboratories and physical facilities; however, the SUCs in Region V met the minimum requirements set by CHED